1992
DOI: 10.1021/bi00158a002
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-specific monoclonal antibodies inhibit DNA replication in mammalian cells

Abstract: The involvement of calmodulin in the proliferation of Chinese hamster embryo fibroblast cells has been studied with a specific monoclonal antibody to calmodulin. We observed that calmodulin levels increase 2-fold in the late G1 period in these cells, and this coincides with the increase in DNA polymerase alpha activity as the cells progress synchronously from a quiescent state in the G1 to the S phase. However, there is a concurrent 10-fold enhancement of thymidine kinase activity, which is tightly coupled to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…13 In addition, microinjection of monoclonal antibodies against CaM inhibited the synthesis of DNA in a dose-dependent manner. 14 Moreover, progression through G 1 and mitosis exit was observed to be sensitive to changes in the intracellular concentration of CaM. 15 Other reports specifically supported a role for CaM in the G 1 /S transition.…”
Section: Ca 2+ /Cam Play a Role In Cell Cycle Progressionmentioning
confidence: 98%
“…13 In addition, microinjection of monoclonal antibodies against CaM inhibited the synthesis of DNA in a dose-dependent manner. 14 Moreover, progression through G 1 and mitosis exit was observed to be sensitive to changes in the intracellular concentration of CaM. 15 Other reports specifically supported a role for CaM in the G 1 /S transition.…”
Section: Ca 2+ /Cam Play a Role In Cell Cycle Progressionmentioning
confidence: 98%
“…Calmodulin is a Ca 2+ binding protein that acts as a Ca 2+ sensor in the cell cycle. High expression of calmodulin has been observed during the S phase and mitosis, while inhibition of its activity by administration of calmodulin monoclonal antibodies is shown to block DNA synthesis [17] . Another sensory mechanism occurs through an extracellular calcium ion concentration sensing receptor (CaR) and calbindin, a high affinity Ca 2+ -binding regulatory protein belonging to the same family as calmodulin.…”
Section: Cyclingmentioning
confidence: 99%
“…chlorpromazine, inhibit electrical uncoupling in Xenopus embryos [14,15] and in epidermal cells [16]. Calmodulin antagonists and antibodies inhibit cell proliferation [17], an effect which may be related to efficacy of gap-junction-mediated communication, since there is increasing evidence that there is a direct correlation between the functional expression of connexins and growth control in cells transfected with connexin genes [18]. Other more direct biochemical approaches have also shown that calmodulin binds to intact gap junctions and tryptic fragments of rat liver connexin 32 in a Ca# + -independent manner [6,19].…”
Section: Introductionmentioning
confidence: 99%